Mass spectrometric exploration of phytohormone profiles and signaling networks - Chen, Y.; Wang, Y.; Liang, X.; Zhang, Y.; Fernie, A. R.
Phytohormones have crucial roles in plant growth, development, and acclimation to environmental stress; however, measuring phytohormone levels and unraveling their complex signaling networks and interactions remains challenging. Mass spectrometry (MS)has revolutionized the study of complex biological systems, enabling the comprehensive identification and quantification of phytohormones and their related targets. Here, we review recent advances in MS technologies and highlight studies that have used MS to discover and analyze phytohormone-mediated molecular events. In particular, we focus on the application of MS for profiling phytohormones, elucidating phosphorylation signaling, and mapping protein interactions in plants.
Keywords: ABA; BRASSINOSTEROID; METABOLOMICS; PLANT HORMONE; PROTEIN PHOSPHORYLATION; PROTEOMICS